Association of Unhealthy Exercise Patterns with Overweight and Obesity in Kuwaiti Adults. - Ahmad R Allafi; Carol Waslien (Tehran University of Medical Sciences, 2014)
Our aim was to investigate the frequency of the behaviors that are most often associated with excess weight gain in Kuwaitis and to determine which gender and age groups are at highest risk for each behavior.A questionnaire developed to identify barriers to exercise in western populations was modified for use with Kuwaitis and posted online during September through December 2012. Data from 1370 adults 18 to 59 years old with BMIs ranging from 15.1-70.8 was collected. The prevalence of seven behavior patterns was examined for age, BMI, and gender groups as well as the odds ratio of each behavior for each BMI group.Both individual unhealthy exercise behaviors and the sum of all such behaviors were more frequent in over-weight and obese individuals. For all behaviors the odds ratio was significantly greater for those with BMIs of 30-39 than for those with BMIs below 25 (P< 0.05). Some exercise avoidance behaviors were more frequent in older age groups and in overweight females.Unhealthy exercise behavior patterns were highly prevalent in obese individuals. Tailoring programs and counseling to the most common of these patterns in Kuwaiti obese should facilitate greater success in weight management.